Basics of Psychic and Cultural Human Deprivation - Terletska, Yulianna M. (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the study is due to the fact that the culture of society, depending on how it is represented in the person psyche, significantly influences the formation of his personality, largely regulates behaviour, inducing either to social solidarity, unity, stability, etc., or to conflicts, confrontation and offenses. The aim of the article is to substantiate the essence of psychic and cultural deprivation of a person of modern society and to reveal its basic aspects. Psycho-energy and energy-psycho-functional approaches were used to achieve the aim. Psychic and cultural deprivation of a person has been proved to be to a greater or lesser extent a destructive process of functioning of his psyche, which has arisen as a result of either destruction and/or contradiction between the inner psychic of different content and significance, which was formed in his psyche under the influence of the external psychic – previous and present elements or complexes, or the absence of an inner psychic, reflecting certain cultural values and norms that should in one way or another be involved in communication, behaviour and activity; the following subspecies of psychic and cultural deprivation have been revealed: dominant, ethnic, group, value-normative, retritistic, literary-artistic, tonic, visual, spatial-plastic, decorative-use, synthetic and choreographic. Knowledge of the essence of psychic and cultural deprivation of a person and disclosure of its main aspects will allow exerting adequate psychological influence in order to eliminate negative mental formations, promote painless adaptation to the new cultural environment, prevent conflicts, offenses and confrontation.